Economic Potential Analysis Of Sugar Palm Cultivation As A Source Of Sap In Jambu Malea Village, Tapango Sub-District - Samad , Wahyu; Ansyar , Ansyar; Hamsah , Hamsah (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study was conducted to analyze the economic potential of sugar palm cultivation in supporting the palm sugar industry in Jambu Malea Village, Tapango Sub-district. The background of this research lies in the considerable potential of sugar palm trees as a source of raw material for palm sugar, which has a high market value. However, its development still faces challenges such as limited cultivation technology, restricted market access, and farmers’ lack of knowledge. The objectives of this study are to examine the income of palm sugar businesses, identify the economic potential of sugar palm cultivation, and assess its prospects for improving community welfare. The research employed a quantitative approach using a survey technique. The sample was determined through a saturated sampling method, in which the entire population of palm sugar entrepreneurs, consisting of 10 individuals, was included as respondents. The data collected comprised production costs, revenue, and income, which were then analyzed descriptively by calculating the total cost, revenue, and business profit. The results revealed that the average palm sugar production reached 429 kg per month with a selling price of IDR 18,000/kg, generating a total revenue of IDR 7,722,000. After deducting the total cost of IDR 1,986,733, the average net income obtained was IDR 5,735,267 per month. These findings indicate that sugar palm cultivation has significant economic potential and is feasible to be developed. Moreover, palm sugar enterprises contribute to increasing community income and hold the potential to support sustainable village development.